Self-perceived risk and barriers to cervical cancer screening among patients seeking care at a tertiary care teaching hospital in Tamil Nadu - Jayaraman, Lokeshwari; K., Maheshwari; Khichi, Sanjeev Kumar; Singh, Abhishek; Goel, Shewtank; Roy, Avijit; K., Jayaprakash; Goyal, Pooja (International Journal of Research in Medical Sciences, 2016)
Background: Identification of characteristics of women, their perceptions of own risk and barriers to accessing existing screening services can provide important information for shaping screening services. The objective of the study was, the present study was undertaken to ascertain the perceptions of risk and barriers to cervical cancer screening by women seeking care at a tertiary care teaching hospital in Tamil Nadu. Methods: The current survey was planned and executed by the Department of Obstetrics and Gynecology of a tertiary care teaching institution of Tamil Nadu during February to July 2015 using a pre-designed questionnaire among 177 study participants. Inclusion criteria were 18 years and above, non-pregnant and consenting for the survey. Women seeking the antenatal care were excluded from this study. The study population consisted of women seeking family planning services at Obstetrics and Gynecology Department. Results: The traditional risk factors for development of cervical cancer were observed in a considerable proportion of the study participants. Sexual debut earlier than 20 years was very common mentioned by nearly 67% of participants. Majority of study participants i.e. more than 50% had multiple sexual partners. About 32% of the study subjects felt that they were at no risk of developing cervical cancer and 34.5% felt no need for screening for the condition. Of women perceiving themselves to be at risk of cancer of the cervix, 80% expressed the need for cervical cancer screening compared to 58.75% of those who had no opinion on own risk. Conclusions: self-perception of not being at risk is documented to be associated with low uptake of screening. Concerned health education programs need to bring clearly to the end user the difference between precancerous lesions and invasive cervical cancer and the treatment options available.